Learners’ Beliefs and Teachers’ Practice of Grammar-focused Written Corrective Feedback in the Malaysian Primary ESL Classrooms : A Pilot Study - Pui, Kuet Poh; Pung, Wun Chiew; Ho, Ai Ping (De La Salle University, 2023)
Written corrective feedback (WCF) is utilized by language teachers to address learners’ mistakes in writing. Although WCF studies should strike a balance between the viewpoints of teachers and learners, studies that focused on learners, especially young learners, have been limited. This study investigated Malaysian primary school learners’ beliefs of how they would like to receive written corrective feedback to grammatical mistakes (GWCF) in their essays, as well as what teachers actually did when providing GWCF in learners’ essays. Findings from the survey showed that the majority of the learners believed all the grammatical mistakes in writing should be indicated and given direct feedback, while analysis of teachers’ GWCF provision in learners’ essays indicated that all the essays were given comprehensive feedback and the majority of the grammatical mistakes were given direct GWCF. The findings also revealed that the learners’ GWCF beliefs aligned with the teachers’ actual practice in terms of scope and types. This study hopes to probe primary ESL teachers to reflect on their current feedback practices in the classrooms while the teachers are encouraged to attend more WCF-related training to enhance the quality of feedback provision. Discussions with the learners can also be carried out to source for appropriate forms of GWCF.